Development of Vocational Education Based on Independent Curriculum at BIM Jombang Center of Excellence Vocational School - Muhammad Nur Hakim; Sania Maria Faradila Mabdalif; Achmad Krisbiyanto; Warti'ah; Ari Kartiko (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2024)
The independent curriculum is structured and organized as a refinement of the previous curriculum with a more dynamic and adaptive learning approach. It frees educators and students to carry out a learning process that continues to develop based on religious values, community culture, and Pancasila. The Government authorizes each SMK PK to plan and implement an independent curriculum focusing on students. The focus of this research is (1) How is the independent curriculum planning in the development of vocational education at SMK PK BIM Jombang, (2) How is the implementation of the independent curriculum in the development of vocational education at SMK PK BIM Jombang? This research method uses descriptive qualitative techniques in data collection triangulation, data reduction, data presentation, and drawing conclusions and verification. The results of this study are (1) Planning for vocational education curriculum for SMK PK in the independent curriculum by participating in training through IHT, compiling curriculum content, curriculum organization, curriculum content organization preparing methods and strategies in learning carried out by the curriculum development team and all teaching Staff, (2) The implementation of the PK vocational education curriculum in the independent curriculum is still in the second stage of development.